Supervision Increases The Implementation of Sharia Nursing Services - Abdurrouf, Muh.; Puspitasari, Puspitasari; Yustini, Yustini (International Journal of Psychosocial Rehabilitation, 2020)
Sharia nursing services are nursing services provided to patients based on the Koran and hadith, where sharia nursing services exceeds patient expectations to increase patient satisfaction. One of the implementations of sharia nursing services is influenced by supervision conducted by the leadership. The purpose of this study is to analyze the relationship between supervision and the implementation of sharia nursing services. This research method used an analytic survey with the cross-sectional approach; the subjects of this study were nurses at Sultan Agung Islamic Hospital Semarang, 96 respondents chosen by a simple random sampling technique according to the: criteria work period is more than 1 year and nurses with DIII / S1 education strata. The data analysis techniques in this study used the Spearman rank. The results showed a relationship between supervision and the implementation of sharia nursing services with a p-value of 0.01 and a correlation coefficient of 0.451. The better the supervision conducted by the leadership, the better the implementation of sharia nursing services, so for a well-run implementation of sharia nursing services it is necessary to increase the supervision to nurses.